Local multipoint distribution services architecture based on rain profile extracted from meteorological radar - Al-Tabatabaie, Kusay Faisal A. (2013)
The growing demand for high-speed Broadband Wireless Access (BWA) applications has motivated the use of millimetre waves operation in Ka band, point-to-multipoint fixed cellular with a large bandwidth of 0.5–1.55 GHz. This service is also known as Local Multipoint Distribution Service (LMDS). It has the advantages of rapid installation, scalability, high capacity, ease of deployment and low initial infrastructure costs; and could be an attractive alternative to other broadband access technologies. However, the service is limited up to 8 km of coverage area due to line of sight constraints. Co-channel interference and rain attenuation are major limitation factors to system performance. This study is conducted to analyse LMDS performance based on local rain cell profile. The long-term cumulative rainfall rate was obtained from weather radar data. This data is compared with ITU-R recommendation and data from rain gauge network. The influence of rain length distribution probability to different rain rate thresholds had been studied from the database for an area size of 25 km2. The target is to design LMDS that reaches up to 5 km of cell size service with good availability. Four architectures of fixed BWA were investigated in terms of a carrier to interference ratio (C/I) using three types of modulations which are QPSK, 16-QAM and 64-QAM. The rain cell profile results shows that higher rain rates experience shorter rain length. The rain rates at 0.01 percentage of time for radar data in UTM is 106.25 mm/hr and rain length was less than 0.46 km. Besides, during low rain rate events, the LMDS service coverage has better performance than clear sky. This is due to fact that the low rain rates present low attenuation to the desired signal but causes high attenuation to interfering base station signals, resulting in better C/I performance. During heavy precipitation, the effective service coverage area will reach to less than 2 km using QPSK in conventional architecture at 99.99% availability. In addition, the co-channel interference can be reduced by using certain design-rule for various architectures. Moreover, it was observed that by decreasing LMDS cell size, the service coverage performance would improve. Two methods had been proposed to improve the performance. One is to use different architectures namely conventional with 4 frequency reuse, simplex ring relaying and dual ring relaying. The second method is to reduce the LMDS service size, i.e. to determine appropriate cell size which offers 99.99% availability. It showed that, for conventional architecture, 3 km cell size was sufficient to reach the required availability based on local climate. In addition, 5 km service cell size for 99.98% availability can be achieved by using dual ring architecture. All the information are important to present BWA network architectures for Malaysian environment based on rain intensity distribution extracted from radar data.